A loopy view of telomere evolution - de Lange, Titia (Frontiers in Genetics, 2015)
About a decade ago, I proposed that t-loops, the lariat structures adopted by many eukaryotic telomeres, could explain how the transition from circular to linear chromosomes was successfully negotiated by early eukaryotes. Here I reconsider this loopy hypothesis in the context of the idea that eukaryotes evolved through a period of genome invasion by Group II introns.